The Critical Roles of Collaborative Leadership and Motivation: A Study of Effort in Enhancing Performance at Private Senior High Schools in Manado City - Mamahit, Meyke Machrita; M. Momongan, Christy (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study aimed to analyze the influence of collaborative leadership style on teachers’ performance at Private Senior High Schools in Manado City, the influence of work motivation on teachers’ performance at Private Senior High Schools in Manado City, and the influence of collaborative leadership style and work motivation as simultaneously on teachers’ performance at Private Senior High Schools in Manado City. The research was conducted at 13 Private Senior High Schools in Manado City. The study utilized a quantitative approach with descriptive survey method and multiple linear regression analysis. Data was collected using a questionnaire, and documents. The sample size was 64 teachers, which were taken using proportionally and randomly from a population of 211 teachers. The findings of the study showed that there was a positive effect of collaborative leadership style on teachers’ performance at Private Senior High Schools in Manado City, there was a positive effect of work motivation on teachers’ performance at Private Senior High Schools in Manado City, and there were the positive effects as simultaneously of collaborative leadership style and work motivation on teachers’ performance at Private Senior High Schools in Manado City. This study emphasized the level of effectiveness and adaptability of collaborative leadership style to the situation, condition, and the needs of school members, especially teachers, in its implementation. The implementation of both collaborative leadership style and work motivation that is suitable for the target and goal will increase the work motivation, both intrinsic and extrinsic. Adaptive and effective collaborative leadership style and high motivation as simultaneously, will give positive effect on improving teacher performance.